2002
DOI: 10.1007/s10142-002-0050-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression during seed germination in barley (Hordeum vulgare L.)

Abstract: A barley cDNA macroarray comprising 1,440 unique genes was used to analyze the spatial and temporal patterns of gene expression in embryo, scutellum and endosperm tissue during different stages of germination. Among the set of expressed genes, 69 displayed the highest mRNA level in endosperm tissue, 58 were up-regulated in both embryo and scutellum, 11 were specifically expressed in the embryo and 16 in scutellum tissue. Based on Blast X analyses, 70% of the differentially expressed genes could be assigned a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
73
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 10 publications
8
73
1
Order By: Relevance
“…Genes involved in stress and defense response made up a major portion of diVerentially expressed transcripts in all four malting stages studied. Previous studies of germinating barley seeds have reported similar Wndings (Potokina et al 2002;Watson and Henry 2005;White et al 2006). This is not surprising since malting is not performed under aseptic conditions and barley seeds contain an inherent microbial Xora consisting of fungi, bacteria, and yeasts (Flannigan 2003).…”
Section: Transcript Prowles Of Germinating Barley Seedssupporting
confidence: 59%
See 1 more Smart Citation
“…Genes involved in stress and defense response made up a major portion of diVerentially expressed transcripts in all four malting stages studied. Previous studies of germinating barley seeds have reported similar Wndings (Potokina et al 2002;Watson and Henry 2005;White et al 2006). This is not surprising since malting is not performed under aseptic conditions and barley seeds contain an inherent microbial Xora consisting of fungi, bacteria, and yeasts (Flannigan 2003).…”
Section: Transcript Prowles Of Germinating Barley Seedssupporting
confidence: 59%
“…DiVerentially expressed genes during germination in barley were also studied using cDNA arrays (Potokina et al 2002;Watson and Henry 2005). Using serial analysis of gene expression (SAGE) to conduct transcript proWling during malting in barley, the most abundant transcripts identiWed by (White et al 2006) overlapped with most genes identiWed in cDNA array-based studies (Potokina et al 2002;Watson and Henry 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Germination of seeds is a multi-stage process requiring the coordinated expression of numerous genes in different tissues (POTONIKA et al, 2002). Under favorable conditions, seeds begins to germinate and the embryonic tissues resume growth, developing into seedlings, with germination being completed when a part of the embryo, the radicle, extends to penetrate the structures surrounding it (BEWLEY, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…While the processes and genes regulating embryogenesis and maturation are being identified (Errampalli et al, 1991;Girke et al, 2000;BrocardGifford et al, 2003;Gallardo et al, 2003;Tzafrir et al, 2003), only very recent studies addressed the question of the exact requirements for germination, particularly in terms of de novo RNA and protein syntheses (Bradford et al, 2000;Bove et al, 2001;Gallardo et al, 2001Gallardo et al, , 2002aKoornneef et al, 2002;Potokina et al, 2002;van der Geest, 2002;Duque and Chua, 2003;Jabrin et al, 2003;Ogawa et al, 2003). Although it is widely documented that, in addition to the storage proteins, mature dry seeds accumulate during maturation a number of proteins that are involved in various cellular processes such as DNA replication and transcription, translation, metabolism, or defense mechanisms (e.g.…”
mentioning
confidence: 99%